The importance of using public data to validate reported associations - Chenevix-Trench, Georgia; Beesley, Jonathan; Pharoah, Paul D. P.; Berchuck, Andrew (PLoS genetics, 2018)
About the Authors: Georgia Chenevix-Trench Roles Conceptualization, Writing – original draft * E-mail: georgiaT@qimr.edu.au Affiliation: Queensland Institute of Medical Research Berghofer, Herston, Queensland, Australia ORCID logo http://orcid.org/0000-0002-1878-2587 Jonathan Beesley Roles Writing – review & editing Affiliation: Queensland Institute of Medical Research Berghofer, Herston, Queensland, Australia Paul D. P. Pharoah Roles Writing – original draft Affiliation: Centre for Cancer Genetic Epidemiology, Department of Public Health and Primary Care, University of Cambridge, Strangeways Research Laboratory, Cambridge, United Kingdom Andrew Berchuck Roles Writing – review & editing Affiliation: Department of Obstetrics and Gynecology, Duke University Medical Center, Durham, North Carolina, United States of America Citation: Chenevix-Trench G, Beesley J, Pharoah PDP, Berchuck A (2018) The importance of using public data to validate reported associations.The results published here are in part based upon data generated by The Cancer Genome Atlas Pilot Project established by the National Cancer Institute and National Human Genome Research Institute (dbGap accession number phs000178.v8.p7).In an analysis by the Ovarian Cancer Association Consortium (OCAC) [2], in over 25,000 ovarian cancer cases and 40,000 controls, no significant association was found for overall ovarian cancer risk (P = 0.24) or for any histological subtypes examined (P = 0.20 for high-grade serous ovarian cancer).